1974
DOI: 10.1111/j.1471-4159.1974.tb06925.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Dietary Protein on Brain Glutamate Dehydrogenase and Decarboxylase in Young Albino Rats

Abstract: Studies were carried out to identify the minimum levels of protein (casein) needed in the diet in order to prevent or reverse the deficits in brain enzymes previously found with protein deficiency. Groups of weanling albino rats were fed diets containing variable amounts of protein (5, 8, 10. 15 or 20 per cent in experiment I, and 5, 6,7, 8 or 20 per cent in experiment 11) for 5 or 10 weeks. Deficits in brain wt and brain glutamate dehydrogenase and decarboxylase were found to be prevented by a diet containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The brain homogenate was assayed for DNA and RNA by the method of Schneider (1957): protein was determined by the method of Lowry et al (1951) and free 01amino nitrogen by the method of Goodwin (1968). Enzymes of glutamic acid metabolism, glutamine synthetase (1.-glutamate: ammonia ligase, E C 6.3.1.2), glutamine transferase (phenylacetyl-COA:L-glutamine a-N-phenylacetyltransferase, E C 2.3.1.141, glutaminase I ( Lglutamine aminohydrolase, E C 3.5.1 .2), glutaminase 11 (i-glutamine:Z-oxoacid aminotransferase, E C 2.6.1.15) were assayed by the methods described by Rajalakshmi et al (19651, and glutamate decarboxylase (L-glutamate 1carboxylyase, EC 4.1.1.15) was assayed after the addition of Triton X-100 (2.5 mg/ml of homogenate) according to the method of Rajalakshmi et al (1974). The estimation of free amino acids related to glutamate metabolism was carried out by paper chromatography employing the method described by Dravid and Jilek (1965).…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…The brain homogenate was assayed for DNA and RNA by the method of Schneider (1957): protein was determined by the method of Lowry et al (1951) and free 01amino nitrogen by the method of Goodwin (1968). Enzymes of glutamic acid metabolism, glutamine synthetase (1.-glutamate: ammonia ligase, E C 6.3.1.2), glutamine transferase (phenylacetyl-COA:L-glutamine a-N-phenylacetyltransferase, E C 2.3.1.141, glutaminase I ( Lglutamine aminohydrolase, E C 3.5.1 .2), glutaminase 11 (i-glutamine:Z-oxoacid aminotransferase, E C 2.6.1.15) were assayed by the methods described by Rajalakshmi et al (19651, and glutamate decarboxylase (L-glutamate 1carboxylyase, EC 4.1.1.15) was assayed after the addition of Triton X-100 (2.5 mg/ml of homogenate) according to the method of Rajalakshmi et al (1974). The estimation of free amino acids related to glutamate metabolism was carried out by paper chromatography employing the method described by Dravid and Jilek (1965).…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…Additionally, the similarities in the response to pharmacological treatment suggest that the GABAbenzodiazepine receptor system could be similarly affected by protein and protein-calorie malnutrition. In the case of protein malnutrition, it has been systematically reported that there are changes in the levels of glutamic acid decarboxylase and GABA and in the number ofbenzodiazepine receptors in several brain areas (Agarwal, Prassad, & Taneja, 1981; Blatt, Rosene, Johnson, & Rajalakshmi, Parameswaran, & Ramakrishnan, 1974;Rajalakshmi, Parameswaran, Telang, & Ramakrishnan, 1974;Telang, Fuller, Wiggins, & Enna, 1984;, supporting the interpretation that these alterations are underlying changes in the reactivity of malnourished animals to the benzodiazepine anxiolytics (Almeida et aI., 1988;Almeida et aI., 1990Almeida et aI., , 1991Almeida et aI., 1996a;Santucci et aI., 1994). Unfortunately, there are few and inconclusive data in the literature on the effects of the protein-calorie malnutrition upon neurochemical and structural parameters of the central GABA-benzodiazepine neurotransmitter system (Rathbun & Druse, 1985).…”
Section: Discussionmentioning
confidence: 99%